Decision-Making Model of Public Service Facility Configuration in Multi-agent Communities and Its Application - 武田艳 严韦 占建军 (东华大学学报（英文版）, 2016)
The decision.making process of the public service facility configuration in multi.agent community is usually simplistic and static. In order to reflect dynamic changes and interactions of all behavior subjects induding of residents, real estate developers and the government, a decision-making model of public service facility configuration according to the multi-agent theory was made to improve the efficiency of the public service facility configuration in community and the living quality of residents. Taking a community to the cast of Jinhui Port in Fengxian District in Shanghai for example, the model analyzed the decision-makers＇ adaptive behaviors and simulated the decision.making criteria. The results indicate that the decision-making model and criteria can be well of satisfying the purpose of improving validity and rationality of public service facility configuration in large community.